ANALISIS PENGGUNAAN BAHASA PROKEM DALAM NOVEL DIKTA DAN HUKUM KARYA DHIA'AN FARAH - Lestari, Vedra Dita; Widayati, Wahyu; Tobing, Victor Maruli Tua L (LPPM Universitas PGRI Silampari Lubuklinggau, 2023)
This study discusses the form of prokem language. The purpose of this study is to describe the form of prokem language in the novel Dicta and Law by Dhia'an Farah. The method used in analyzing data is qualitative method. Data collection techniques in this study use basic reading techniques, and advanced techniques, namely recording techniques. The data analysis techniques used are the distribution method and the basic technique using the technique for direct elements (BUL) and advanced techniques using lethargy and replace techniques. The results of the analysis obtained in this study are in the form of prokem language forms in the novel Dicta and Law by Dhia'an Farah in the form of basic words, affix words, clauses, phrases, acronyms, abbreviations and letter insertions.